Rapid Trio Exome Sequencing for Autosomal Recessive Renal Tubular Dysgenesis in Recurrent Oligohydramnios - Lin, Shin-Yu; Chuang, Gwo-Tsann; Hung, Chien-Hui; Lin, Wei-Chou; Jeng, Yung-Ming; Yen, Ting-An; Chang, Karine; Chien, Yin-Hsiu; Hwu, Wuh-Liang; Lee, Chien-Nan; Tsai, I-Jung; Lee, Ni-Chung (Frontiers in Genetics, 2021)
Oligohydramnios is not a rare prenatal finding. However, recurrent oligohydramnios is uncommon, and genetic etiology should be taken into consideration. We present two families with recurrent fetal oligohydramnios that did not respond to amnioinfusion. Rapid trio-whole-exome sequencing (WES) revealed mutations in the AGT gene in both families within one week. The first family had a compound heterozygous mutation with c.856+1G>T and c.857-619_1269+243delinsTTGCCTTGC changes. The second family had homozygous c.857-619_1269+243delinsTTGCCTTGC mutations. AGT gene mutation may lead to autosomal recessive renal tubular dysgenesis, a rare and lethal disorder that can result in early neonatal death. Both the alleles identified are both known alleles associated with pathogenicity. Our findings suggest that trio-WES analysis may help rapidly identify causative etiologies that can inform prompt counseling and decision-making prenatally.